Recovery of Polyphenols from Vineyard Pruning Wastes-Shoots and Cane of Hybrid Grapevine (Vitis sp.) Cultivars - Reelika Rätsep; Kadri Karp; Mariana Maante-Kuljus; Alar Aluvee; Hedi Kaldmäe; Rajeev Bhat (MDPI AG, 2021)
Grapevine shoots and canes represent a significant amount of biomass, considered as a waste in viticulture. In cooler climates, grapevines are pruned in the autumn (October) and spring (March) due to harsh winter conditions (e.g., snow, low temperatures), and large amounts of biomass are produced at these different pruning times. This work was undertaken in order to investigate the potential of vineyard pruning waste for recovery of polyphenolic compounds for biomass valorization. Qualitative and quantitative analyses of grapevine shoot and cane polyphenols, including flavonoids and stilbenoids were performed using UHPLC MS/MS method. The results revealed the flavonols (quercetin) to be the most abundant compounds in shoots among all the three cultivars screened (Zilga, Hasansky Sladky, Rondo). Stilbenoids (ε-viniferin) dominated in the canes, while increased level of flavonols with lower contents of stilbenoids was detected in the endo-dormant canes, and higher amounts of flavanols and stilbenoids were recorded in eco-dormant canes. In conclusion, the content of polyphenols in grapevine shoots and canes differed among the cultivars and dormancy phases. The results generated from the present study contribute to the sustainable and environmentally friendly viticulture practice via valorization of vineyard pruning wastes.